2019
DOI: 10.1111/tpj.14279
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of lincRNA transcription in nine citrus species

Abstract: Summary Long intergenic non‐coding RNAs (lincRNAs) play important roles in various biological processes in plants. However, little information is known about the evolutionary characteristics of lincRNAs among closely related plant species. Here, we present a large‐scale comparative study of lincRNA transcription patterns in nine citrus species. By strand‐specific RNA‐sequencing, we identified 18 075 lincRNAs (14 575 lincRNA loci) from 34 tissue samples. The results indicated that the evolution of lincRNA trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Target mimicking of miRNA is one of the most important mechanisms of lncRNAs regulating the plant development 11,42 . In other plant species, such as chickpea, Arabidopsis, citrus, rice, canola and maize, it was shown that lncRNAs also could act as miRNA targets, miRNA precursors or endogenous target mimics 34,[42][43][44][45][46] . To sum up, the interaction between lncRNAs and miRNAs could be an important posttranscriptional regulatory mechanism for gene regulation in the developing seeds of Jatropha.…”
Section: Identification Of J Curcas Lncrnas and The Characteristic Fmentioning
confidence: 99%
“…Target mimicking of miRNA is one of the most important mechanisms of lncRNAs regulating the plant development 11,42 . In other plant species, such as chickpea, Arabidopsis, citrus, rice, canola and maize, it was shown that lncRNAs also could act as miRNA targets, miRNA precursors or endogenous target mimics 34,[42][43][44][45][46] . To sum up, the interaction between lncRNAs and miRNAs could be an important posttranscriptional regulatory mechanism for gene regulation in the developing seeds of Jatropha.…”
Section: Identification Of J Curcas Lncrnas and The Characteristic Fmentioning
confidence: 99%
“…Furthermore, nta-eTMX27 in Nicotiana tabacum , osa-eTM160 in Oryza sativa (Wang et al, 2017a), lncRNA23468 in Solanum lycopersicum (Jiang et al, 2019), and LTCONS-00042843 in Dimocarpus longan (Chen et al, 2018a) are eTMs that modulate target gene expression by functioning as decoys for relevant miRNAs. The development of high-throughput sequencing and bioinformatics tools enabled the identification of many lncRNAs in several plant species, including model plants like A. thaliana (Yuan et al, 2016), O. sativa (Zhang et al, 2014;Wang et al, 2018a), and Brachypodium distachyon (Quattro et al, 2017), and also in horticultural plants such as S. lycopersicum (Zhu et al, 2015), Cucumis sativus (Hao et al, 2015), Musa itinerans (Liu et al, 2018a), D. longan (Chen et al, 2018a), and Citrus sinensis (Ke et al, 2019). Moreover, lncRNAs in plants help regulate secondary metabolism and stress responses Zhang et al, 2018;Liu et al, 2018a;Wang et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…by high-throughput sequencing, of which the number varied from tens to tens of thousands 59 . In citrus, we only found that Ke et al 60 identified 1238 (Citrus paradisi) to 3285 (Atalantia buxifolia) lncRNAs in nine citrus species, and Wang et al 61 identified a total of 6584 potential lncRNAs in trifoliate orange. In addition, Zeng et al 62 identified 558 potential circRNAs in trifoliate orange.…”
Section: Possible Function Of Lncrna and Circrna In Citrus Cu Toxicitymentioning
confidence: 66%